Disorganisation in the transition process: Firm level evidence from Ukraine - Jozef Konings; Patrick Paul Walsh (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
Most post-communist economies are characterized by an initial collapse in aggregate output. Blanchard and Kremer (1997) and Roland and Verdier (1997) have recently modelled supply side distortions, disorganization in the links of production, that can lead to a short-term output contraction after market liberalisation and a recovery thereafter. This paper is the first to illustrate and test the effects of disorganization in the transition process by using a unique data set of 300 Ukrainian firms. Our results show that for firms that existed under central planning disorganization constrains employment and productivity growth during the transition process to a market economy. In contrast, disorganization plays no role in the determination of employment and productivity growth in newly established private firms.
Keywords: P0; O0; D0; 330; disorganization; transition process; de novo firms